Profitability and resource rent of multi-gear fisheries in Lagonoy Gulf, Philippines - Bradecina, Raul G.; Soliman, Victor S.; Dioneda, Ronnel R.; Dioneda, Ronnel R., Sr.; Pelea, Ninfa R. (2011)
We evaluated the profitability and resource rent of multi-gear fishery in Lagonoy Gulf, Philippines. Fishing costs obtained from socioeconomic survey and estimates of revenue from gear inventory and catch surveys were used in the benefit-cost analysis. An estimated annual revenue of PhP 1,035 million was obtained from the 26,000 mt production of multi-gear fishery in 2004. The quality of catch and the costs of fishing defined the differential profitability. Total cost was valued at PhP 598 million. The large opportunity cost of labor reconfirmed the economic significance of subsistence fishery as source of employment. Pure profit or resource rent of PhP 466 million was generated from the resource. The use of unsustainable gears and excess capacity eroded fishers' profitability and dissipated resource rent. Unsustainable gears derived negative returns from the fishery, amounting to PhP 168 million. More benign gears were found to be economically profitable, posting positive returns totalling PhP 634 million. However, their excess numbers constrained economic and ecological sustainability. Banning unsustainable gears, imposing higher license fees and reducing effort based on gears are recommended control mechanisms to address use of unsustainable gears and excessive efforts. Establishment of cluster of marine protected areas for resource regeneration and governance is a complementary strategy to address economic overfishing in the area in the current context of its socioeconomic and cultural realities.
Keywords: Fisheries; Lagonoy Gulf